Interactive intragroup tutorials: a need-based modification to enhance learning in physiology - Srivastava, Tripti K.; Waghmare, Lalitbhushan S.; Jagzape, Arunita; Mishra, Vedprakash (Advances in physiology education, 2015)
A tutorial is a period of instruction given by a university or college tutor to an individual or a very small group. Essentially, it is a small class of a few students in which the tutor (a lecturer or other academic staff member) gives individual attention to every learner. The tutorial focuses on certain subject areas and generally proceeds with careful reading of selected primary texts and working through associated exercises. In this article, the authors discuss interactive group tutorials and how they have been incorporated into the physiology curriculum.